Evaluation of Dabigatran Bleeding Adverse Reaction Reports in the FDA Adverse Event Reporting System during the First Year of Approval. Issue 6 (19th March 2014) - McConeghy, Kevin W.; Bress, Adam; Qato, Dima M.; Wing, Coady; Nutescu, Edith A.
<x xml:space="preserve">Abstract</x> Study Objective Evaluate dabigatran adverse event reports with a reported bleeding event and/or reported fatal outcome compared with warfarin. Design Retrospective analysis of the FDA Adverse Event Reporting System (FAERS) database. Measurements and Main Results We identified reports from October 1, 2010, through December 31, 2011, in the United States listing dabigatran or warfarin as the primary suspected agent. Bleeding events and related outcomes were determined. A bleeding‐related mortality rate was calculated based on national dabigatran treatment data. Results Dabigatran was the primary suspected agent in 9029 adverse reports. Of these, 2347 (26%) were bleeding events; a fatal outcome was reported in 348 (15%) of the bleeding events. In comparison, warfarin was the suspected agent in 2038 reports, of which 647 (32%) were reported as bleeding events. Among the warfarin bleeding reports, 46 (7.1%) reported a fatal outcome. Based on national dabigatran use and adverse bleed reports with fatal outcomes, we estimate a lower bound of 150 bleeding‐related fatalities per 100, 000 dabigatran patient‐years. Because of underreporting bias, these estimates represent a lower bound on the population bleeding mortality rates. Conclusion Reports from FAERS are subject to significant bias but suggest that fatal outcomes among dabigatran reports are higher in clinical practice than they were in controlled clinical trials.